2007
DOI: 10.1017/s0025315407057724
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of three eyeless Chaetozone species (Cirratulidae: Polychaeta) in the north-east Atlantic

Abstract: Geographical information system analysis was applied to assist in the re-identification of records of Chaetozone setosa from the north-east Atlantic. Previously this species was considered to have a world-wide distribution. The aim of this study is to clarify and illustrate the distribution patterns associated with sediment and water characteristics of C. setosa and other Chaetozone species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… Eyespots absent 2 Eyespots present 4 Very long capillary setae (2–3 times body width) present from setiger 2 or from ~setiger 20; well-defined constrictions (about half of setiger width) between posterior setigers 3 No setae longer than body width; slight constrictions (about 1/5 of setiger width) between posterior setigers Chaetozone christiei Chambers, 2000 Very long capillary setae present from the setiger 2; 12–14 spines in each ramus in posterior setigers Chaetozone jubata Chambers & Woodham, 2003* Very long capillary setae present from ~setiger 20; 6–8 spines in each ramus in posterior setigers Chaetozone setosa Malmgren, 1867 Very long capillary setae, longer than body width; constrictions well marked between posterior setigers 5 No setae longer than body width; constrictions few between posterior setigers 6 Notopodial spines start from setigers 1–9 and neuropodial spines start from setiger 1; first pair of branchiae on the peristomium Chaetozone corona Berkeley & Berkeley, 1941 Noto- and neuropodial spines start from setigers 6–9; two types of spines present: (1) large and up to 0.5 mm long from anterior to mid-body region and (2) narrower and up to 4 mm in posterior part; first pair of branchiae on the first setiger Chaetozone carpenteri McIntosh, 1911 Body surface iridescent; anterior dorsal surface rounded; thick posterior spines only in neuropodia; notopodia with awl-shaped spinous setae Chaetozone zetlandica McIntosh, 1911 Body surface opaque; thick spines in posterior notopodia and neuropodia 7 Anterior dorsal surface with obvious hump; neuropodial spines from anterior region (setigers 50–80) to end of body; notopodial spines from mid-body (setigers 90–100) Chaetozone gibber Woodham & Chambers, 1994 Anterior dorsal surface without hump; neuropodial spines from setigers 10–13 Chaetozone caputesocis (de Saint-Joseph, 1864)** *deep-sea species (from 350 to 1800 m depth) (Chambers et al , 2007). **de Saint-Joseph (1894) wrote that Chaetozone caputesocis possess notopodial spines in the last 23 setigers only, whereas Hartmann-Schröder (1996) mentioned the presence of notopodial spines from setiger 16: ‘Ab 10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Eyespots absent 2 Eyespots present 4 Very long capillary setae (2–3 times body width) present from setiger 2 or from ~setiger 20; well-defined constrictions (about half of setiger width) between posterior setigers 3 No setae longer than body width; slight constrictions (about 1/5 of setiger width) between posterior setigers Chaetozone christiei Chambers, 2000 Very long capillary setae present from the setiger 2; 12–14 spines in each ramus in posterior setigers Chaetozone jubata Chambers & Woodham, 2003* Very long capillary setae present from ~setiger 20; 6–8 spines in each ramus in posterior setigers Chaetozone setosa Malmgren, 1867 Very long capillary setae, longer than body width; constrictions well marked between posterior setigers 5 No setae longer than body width; constrictions few between posterior setigers 6 Notopodial spines start from setigers 1–9 and neuropodial spines start from setiger 1; first pair of branchiae on the peristomium Chaetozone corona Berkeley & Berkeley, 1941 Noto- and neuropodial spines start from setigers 6–9; two types of spines present: (1) large and up to 0.5 mm long from anterior to mid-body region and (2) narrower and up to 4 mm in posterior part; first pair of branchiae on the first setiger Chaetozone carpenteri McIntosh, 1911 Body surface iridescent; anterior dorsal surface rounded; thick posterior spines only in neuropodia; notopodia with awl-shaped spinous setae Chaetozone zetlandica McIntosh, 1911 Body surface opaque; thick spines in posterior notopodia and neuropodia 7 Anterior dorsal surface with obvious hump; neuropodial spines from anterior region (setigers 50–80) to end of body; notopodial spines from mid-body (setigers 90–100) Chaetozone gibber Woodham & Chambers, 1994 Anterior dorsal surface without hump; neuropodial spines from setigers 10–13 Chaetozone caputesocis (de Saint-Joseph, 1864)** *deep-sea species (from 350 to 1800 m depth) (Chambers et al , 2007). **de Saint-Joseph (1894) wrote that Chaetozone caputesocis possess notopodial spines in the last 23 setigers only, whereas Hartmann-Schröder (1996) mentioned the presence of notopodial spines from setiger 16: ‘Ab 10.…”
Section: Resultsmentioning
confidence: 99%
“…Until the late 1990s–early 2000s, most authorities considered that the only Chaetozone species present within North-east Atlantic waters was C. setosa Malmgren, 1867 (Malmgren, 1867; Fauvel, 1927; Gentil & Mora Bermudez, 1976; Hily, 1987; Dauvin et al , 2003). However, C. setosa was originally described from Spitzbergen in the Norwegian Arctic and is now considered to be restricted to the northern waters of Europe, including the Arctic, North Sea and west coast of Scotland (Chambers, 2000; Chambers et al , 2007; Blake, 2015). Moreover, Chambers & Woodham (2003) suggested that C. setosa was a complex of species.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the number of recognized new species is increasing as well. New species from Europe and off the Faroes have been described by Woodham & Chambers (1994), Chambers (2000), and Chambers & Woodham (2003) and others are known (Chambers et al 2007;Doner, unpublished). Magalhães & Bailey-Brock (2013) described two new species of Chaetozone from the Hawaiian Islands and a rich cirratulid fauna from South America and Antarctica includes several new species of Chaetozone (Blake, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 97%
“…Eyes have been reported for several species of Chaetozone (Blake 1996;Woodham & Chambers 1994;Chambers 2000) and are sometimes used to distinguish individual species or groups of species (Chambers et al 2007). However, pigmented cells often surround the nuchal organs and may be mistaken for eyes due to their position and pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, bitentaculate specimens of Chaetozone having posterior spines arranged into cinctures on posterior segments were referred globally to Chaetozone setosa Malmgren, the type species originally described from Spitsbergen, in the Arctic north of Norway. Recently, the elucidation of new characters among species of Chaetozone from North America and elsewhere, and the redescription of C. setosa provided by Chambers (2000), led to descriptions of numerous new species and the identification of distinct species groups (Blake 1996(Blake , 2006Chambers & Woodham 2003;Doner & Blake 2006;Chambers et al 2007). With the realisation that the genus Chaetozone contains numerous species, many of which have gone unrecognised, the greater majority of the older records of C. setosa from worldwide locations are now believed to refer to other taxa (Blake 2015).…”
Section: Introductionmentioning
confidence: 99%